Creative Writing: Short Stories - English - Kenzel, Elaine; Williams, Jean (2023)
Form, content, and style are stressed in this quinmester program in the creative writing of short stories. The program, which is offered )71, the Dade County Public Schools, is designed for students who wish to improve their writing skills in order to compose a structured s.:Iort story. Among the learning activities suggested by the program are awareness exercises; cultivation of sensory experiences; discussions of books, plays and movies; and character study. A resource list ror students and teacher; includes textbooks, reference materials, films, filmstrips, audio tapes, and records.